Efektivitas Pembelajaran PAK Dengan Metode Concept Mapping Berbantuan Media Canva Pada Peserta Didik Kelas XI Multimedia 1 SMK Marsudirini St. Fransisikus Semarang - Alfonsus Ryan Jati Atmaja; Anselmus Joko Prayitno; Sugiyana Sugiyana (Simpati, 2023)
There..are..several..factors that cause the.low skills and learning achievement of PAK students in class XI Multimedia 1 SMK Marsudirini St. Francis Semarang. One of these factors is the way the teacher teaches, which is still teacher-centered and uses the lecture method, which makes students less proficient in PAK learning. so that learning tends to be monotonous, and the resulting formulation..of..the..problem..is as follows: Is learning with the Concept Map method assisted by Canva media effective for increasing students' skills and learning achievement in PAK learning, to discuss this problem, quantitative research is carried out using independent variables: process skills which will be marked X and the dependent variable: learning achievement marked Y with the instruments of observation sheets, tests, and questionnaires, with research subjects being students of class XI Multimedia 1 as the experimental class and class XI Multimedia 2 as the control class. The results of this study were as many as 70.8% of experimental class students achieved a higher mastery score than the control, there was an increase in the average learning achievement in class XI Multimedia 1 by 9.5% before and after learning, and showed the effect of skills on learning achievement of 38.9%, although these results were not dominant, the results were positively distributed so that the use of the Canva media-assisted Concept Map learning method was effective in increasing PAK learning achievement in class XI Multimedia 1.